PENGARUH PENDIDIKAN KESEHATAN REPRODUKSI MELALUI MEDIA AUDIOVISUAL DAN BOOKLET TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG KEPUTIHAN DI FAKULTAS SAINS DAN KESEHATAN UNIVERSITAS ANDI SUDIRMAN TAHUN 2025 - Sumarni Sumarni; Andi Ria Metasari; Susilawati Susilawati; Sriwidyastuti Sriwidyastuti (Nusantara Hasana Journal, 2026)
Adolescence is a transitional period from childhood to adulthood, marked by physical, emotional, and psychological changes. Reproductive health will impact reproductive health if not addressed promptly and effectively. One of the health problems in adolescents is vaginal discharge. Efforts to increase knowledge are carried out by providing health education. Health education is the activity of conveying information about health and instilling confidence so that the public can understand and carry out recommendations (Putinah, 2022). With current technological advances, the use of learning media has become more innovative and creative for learning, thus creating an effective and efficient learning model. Based on the results of the analysis using the Chi-Square statistical test, a P value of 0.000 <P value of 0.05 was obtained. This means that the influence of reproductive health education through audiovisual media and booklets on adolescent girls' knowledge about vaginal discharge.